'Story of a friendship': Alan Bush, Grigorii Shneerson and cultural diplomacy before and during the Cold War. Issue 3 (1st September 2016) - Wiggins, Louise
ABSTRACT: This article explores efforts by the British composer Alan Bush to facilitate cultural exchange from the late 1930s and across the Iron Curtain. I will argue that his unwavering support and championing of Soviet music deserves greater acknowledgement. Through the correspondence between Bush and the Russian musicologist Grigorii Shneerson it has been possible to compile a list of materials exchanged between the two unofficially. It is my intention to draw attention to a small, but not insignificant world of private exchange voluntarily undertaken by individuals such as Bush and to show that such exchanges played an important part in cultural diplomacy between the two countries. From a broader perspective, we will see how their communication was viewed by the British authorities as politically significant, but that for the two men it was predominantly a relationship about music.